Research on Load Torque of Robot Reducer Acceleration Fatigue Tests Based on Adams - Chen Lei; Tong Guiying; Mu Yinyin; Qiao Guipeng (Jixie chuandong)
Accuracy and fatigue life are important factors restricting the development of domestic robot reducers. In order to improve the efficiency of fatigue life test, it is very important to select appropriate load torque for accelerated life test. In this study, according to the real working condition of a certain robot reducer on the industrial robot, the maximum load torque of the robot reducer without failure is obtained through calculation and simulation, and the accelerated life test is completed on the basis of this. Firstly, the calculation model is built by using SolidWorks software, the maximum static torque is calculated and the appropriate load mass is preliminarily selected. Then the Adams software is used to simulate the pendulum of fatigue test load. According to the maximum static torque and the maximum dynamic torque, the load quality and rotation acceleration and deceleration time are calculated. An orthogonal experiment is designed to combine the two to obtain the load mass and rotation acceleration and deceleration time that can complete the accelerated fatigue test with the highest efficiency. Besides, the correctness of simulation calculation is verified by experiments. The results show that the load static torque has a great influence on the test time, and the test time of the robot reducer is significantly shortened after selecting the appropriate load mass, the rotation acceleration and the deceleration time, which improves the test efficiency of robot reducers. It provides a theoretical basis for the accelerated life test of robot reducers.